Answer to Question #96870 in Calculus for Ojugbele Daniel
Differentiate from first principle square root of (x+√x).
1
2019-10-21T10:28:34-0400
"f(x)=\\sqrt{x+\\sqrt{x}}"
"f'(x)=\\bigg(\\sqrt{x+\\sqrt{x}}\\bigg)'=\\lim\\limits_{h\\rarr0}{f(x+h)-f(x) \\over h}="
"=\\lim\\limits_{h\\rarr0}{\\sqrt{x+h+\\sqrt{x+h}}-\\sqrt{x+\\sqrt{x}} \\over h}="
"=\\lim\\limits_{h\\rarr0}{\\sqrt{x+h+\\sqrt{x+h}}-\\sqrt{x+\\sqrt{x}} \\over h}\\cdot{\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}} \\over \\sqrt{x+h+\\sqrt{x+h}}}="
"=\\lim\\limits_{h\\rarr0}{ x+h+\\sqrt{x+h}-x-\\sqrt{x}\\over h(\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}})}="
"=\\lim\\limits_{h\\rarr0}{ h\\over h(\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}})}+"
"+\\lim\\limits_{h\\rarr0}{ \\sqrt{x+h}-\\sqrt{x}\\over h(\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}})}="
"={ 1\\over \\sqrt{x+0+\\sqrt{x+0}}+\\sqrt{x+\\sqrt{x}}}+"
"+\\lim\\limits_{h\\rarr0}{ \\sqrt{x+h}-\\sqrt{x}\\over h(\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}})}\\cdot{\\sqrt{x+h}+\\sqrt{x} \\over \\sqrt{x+h}+\\sqrt{x}}="
"={ 1\\over 2\\sqrt{x+\\sqrt{x}}}+\\lim\\limits_{h\\rarr0}{ x+h-x\\over h(\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}})(\\sqrt{x+h}+\\sqrt{x})}="
"={ 1\\over 2\\sqrt{x+\\sqrt{x}}}+\\lim\\limits_{h\\rarr0}{ 1\\over (\\sqrt{x+h+\\sqrt{x+h}}+\\sqrt{x+\\sqrt{x}})(\\sqrt{x+h}+\\sqrt{x})}="
"={ 1\\over 2\\sqrt{x+\\sqrt{x}}}+{ 1\\over (\\sqrt{x+0+\\sqrt{x+0}}+\\sqrt{x+\\sqrt{x}})(\\sqrt{x+0}+\\sqrt{x})}="
"={ 1\\over 2\\sqrt{x+\\sqrt{x}}}\\big(1+{1 \\over 2\\sqrt{x}}\\big)"
"\\bigg(\\sqrt{x+\\sqrt{x}}\\bigg)'={ 1\\over 2\\sqrt{x+\\sqrt{x}}}\\bigg(1+{1 \\over 2\\sqrt{x}}\\bigg)"
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment